Austria : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
This 2005 Article IV Consultation highlights that economic activity in Austria gathered speed in 2004, supported mostly by strong export performance. Growth of real GDP rose to 2.2 percent in 2004. Consumption growth was modest, in view of small gains in employment and nominal wage growth barely matching inflation. Investment demand continued to expand, benefiting from the improved prospects for exports and the extension of tax incentives through end-2004. Progress in the structural area has been impressive, and this has contributed to Austria's relatively favorable growth performance in the past period.